2021
DOI: 10.3390/horticulturae7030044
|View full text |Cite
|
Sign up to set email alerts
|

Storage Behavior of “Seddik” Mango Fruit Coated with CMC and Guar Gum-Based Silver Nanoparticles

Abstract: Mango fruit (cv. Seddik) is known as a delicate fruit for storage after harvest. Herein, carboxymethyl cellulose (CMC) and guar gum-based silver nanoparticles (AgNPs) were used as fruit coatings, and their effects on postharvest storage behavior and quality attributes were investigated. AgNPs were synthesized using a chemical reduction approach and then combined with CMC and guar gum as coating bases. Mango fruits were coated with the developed and pre-characterized CMC-AgNPs and guar gum-AgNPs, and then packe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 71 publications
5
15
0
Order By: Relevance
“…TEM micrograph demonstrates the formation of spherical shape with a narrow range of particle size distribution, the spherical nanoparticles were produced with size of 5-15 nm (Silver NPs), 15-35 nm (Selenium NPs) and 20-50 nm (Chitosan NPs). Analysis of TEM micrograph demonstrated that, the mean size of the obtained nanoparticles are comparable to the particle size that has been reported in previous studies for silver (Hmmam et al 2021), selenium (Srivastava and Mukhopadhyay 2015), and chitosan nanoparticles (Asgari-Targhi et al 2018). Therefore, the prepared nanoparticle in our study represented typical nanoparticle in term of shape and size.…”
Section: Resultssupporting
confidence: 85%
“…TEM micrograph demonstrates the formation of spherical shape with a narrow range of particle size distribution, the spherical nanoparticles were produced with size of 5-15 nm (Silver NPs), 15-35 nm (Selenium NPs) and 20-50 nm (Chitosan NPs). Analysis of TEM micrograph demonstrated that, the mean size of the obtained nanoparticles are comparable to the particle size that has been reported in previous studies for silver (Hmmam et al 2021), selenium (Srivastava and Mukhopadhyay 2015), and chitosan nanoparticles (Asgari-Targhi et al 2018). Therefore, the prepared nanoparticle in our study represented typical nanoparticle in term of shape and size.…”
Section: Resultssupporting
confidence: 85%
“…The results are in accordance with the study that used the guar gum based AgNPs with carboxymethyl cellulose to enhance the shelf life of mango for 14 days at 25˚C after the spoilage of untreated mango over the total storage period of 28 days [59]. The loss of firmness during storage period was due to the change in banana texture but the coating of silver nano particles slowed down the metabolic and enzymatic activities by inhibiting the respiratory metabolism in the fruits that results a slower degradation of pulp tissues [59,60]. Consequently, bananas stored with AgNPs can retain their firmness by reducing the ethylene production, respiration rate, the speed of converting sugar and decay rate of banana [61].…”
Section: Plos Onesupporting
confidence: 91%
“…Hmmam et al [73] developed carboxymethyl cellulose (CMC) and guar gumbased silver nanoparticles (AgNPs) coatings for "Seddik" mango fruit. Nanoparticles were formed at an average size of 84.8 to 213 nm for CMC-AgNPs and 61.7 to 132 nm for guar gum-AgNPs.…”
Section: Nanoparticles Incorporated In Coatingsmentioning
confidence: 99%